Couples' employment after spousal kidney donation. (26th November 2018) - Frech, Adrianne; Natale, Ginny; Tumin, Dmitry
ABSTRACT: We used data from the United Network for Organ Sharing registry of living kidney donors and recipients to identify correlates of paid employment among couples following spousal living donation. Among such couples, post-transplant employment of both spouses (41%) was as common as employment of the donor only (41%). However, when the recipient was female, donor-only employment after transplant was more than twice as likely as compared to employment of both spouses (relative risk ratio = 2.57; p  < .001). We conclude that traditional gender roles regarding paid workforce participation may be associated with the likelihood of employment after spousal kidney donation.